Ideology, Maqāṣid, and Politics: The Paradox of Al-Qaraḍāwī’s Islamist Thought - Sulaiman, Akhmad; Masrukhin, Mohammad Yunus; Sunaryo, Agus; Zaman, Akhmad Roja Badrus (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2025)
The renewal of maqāṣid (Islamic legal objectives) emphasizes the substance and purpose of the law, in contrast to ideology, which compels adherence to non-negotiable commitments. This study investigates Yūsuf Al-Qaraḍāwī’s reluctance to apply maqāṣid-based hermeneutics to qaṭʿiyyat al-dilālah (texts with definitive meaning), situating this reluctance within the ideological framework of Islamism to which he remained committed. Through a combined textual and contextual analysis of Al-Qaraḍāwī’s writings and relevant secondary literature, the study demonstrates that his resistance to contextual reinterpretation—reinforced by the status of these texts as qaṭʿiyyah al-wurūd—derives from their construction as immutable foundations of orthodoxy that safeguard the unity of the ummah. This stance serves a dual ideological function: it preserves qaṭʿiyyah texts as fixed boundaries within an Islamic polity and mobilizes them as symbols of pan-Islamic solidarity. Although Al-Qaraḍāwī’s vision of a supranational Islamic state evolved into a transnational authority network through the International Union of Muslim Scholars (IUMS), the underlying ideological imperatives of unity and divine sovereignty remained intact. The article concludes that Al-Qaraḍāwī’s thought exemplifies both the possibilities and limitations of maqāṣid reasoning when situated within the doctrinal commitments of Islamism. This study contributes to a deeper understanding of how Islamic legal thought is transformed into an instrument of ideological legitimation within modern Islamic reformism.